Āhnikaṃ : Ācāradīpika enna bhāṣāvyākhyānattōṭukūṭiyatu - Vāsudēvaśarmma, Si. Ke (SAMP early 20th-century Indian books project, 1923)
Translation of Sanskrit prayers for daily rites; includes Ācāradīpika, a commentary by Si. Ke. Vāsudēvaśarmma.